Barrismo popular entre la seguridad, comodidad y convivencia: un análisis comparado sobre el diseño de la política del fútbol en Cali y Medellín (Estudios) - Restrepo Caicedo, Juan Manuel (2019)
This article analyzes how the tenuous participation of non-state actors -fan groups (cheering) - within the “Ten-Year Plan for Safety, Comfort and Coexistence in Soccer (2014- 2024)”, affects its implementation process. Taking into account the perspective of nested theory developed by Howlett and the debate on governance, the article demonstrates policy fragility regarding to its implementation (specifically in resources and organization terms) and the legitimacy and effectiveness absence due to the lack of inclusion; concluding that the development of interactive participatory channels contributes to policy effectiveness. Methodologically, it does a comparative analysis between Cali and Medellin cases.